DOI: 10.18297/etd/1142
|View full text |Cite
|
Sign up to set email alerts
|

International student-athlete perception of college sport and its effect on adjustment to college.

Abstract: This dissertation is dedicated to my loving wife, Stephanie, who has been with me every step of the way as I pursued this goal of completing my doctoral program. She has been incredibly encouraging and understanding throughout the process and she makes the rewards of completion twice as enjoyable.I also would like to dedicate this work to my parents, Rod and Milli, who helped raise me to be both academically inquisitive and a true lover of sports. Without their guidance, I would not be where I am today. compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
(235 reference statements)
0
6
0
Order By: Relevance
“…Other research indicates international student-athletes have different intrinsic motivations as compared to domestic student-athletes (Stokowski, Huffman, & Aicher, 2013). Additionally, adjustment differences exist among both populations, as international student-athletes deal with unique issues such as language barriers (Sato, Hodge, & Burge-Hall, 2011) and other social and academic concerns (Popp, 2008).…”
mentioning
confidence: 99%
“…Other research indicates international student-athletes have different intrinsic motivations as compared to domestic student-athletes (Stokowski, Huffman, & Aicher, 2013). Additionally, adjustment differences exist among both populations, as international student-athletes deal with unique issues such as language barriers (Sato, Hodge, & Burge-Hall, 2011) and other social and academic concerns (Popp, 2008).…”
mentioning
confidence: 99%
“…Regarding the impact of cold and inclement weather on personal emotional adjustment, Searle and Ward (1990) found that religion, language, and climate are often the most important factors separating international students from their new cultural context, causing significant conflict. Popp (2007) also reported that the ISA recognizes climate adjustment as a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The transition into US collegiate sport for ISA not only includes the typical obstacles associated with adapting to college, such as navigating socialization opportunities, experiences of homesickness, or interpreting differences in academic structure, but also those related to joining a new system within sport in an unfamiliar cultural setting. Awareness of potential hindrances, such as communication barriers, role ambiguity, and unfamiliar norms, is essential in order to assertively take action to meet the needs of ISA (Bruner, Munroe-Chandler, & Spink, 2008;Popp, 2007;Pierce et al, 2011). Additionally, coping skills, psycho-social interventions, phases in adaptation, and other approaches to resource development for athlete transitions to advanced training centers have received increasing attention from sport psychologists (e.g., Poczwardowski, Diehl, O'Neil, Cote, & Haberl, 2014;Stambulova et al, 2012;Stambulova, Pehrson, & Olsson, 2017).…”
Section: Introductionmentioning
confidence: 99%